The seismic responses of a rubble mound breakwater - Yuksel, Y.; Berilgen, M.; Cihan, K.; Cevik, E. Ozkan; Dizman, U.; Yalciner, A. C. (INTERNATIONAL SOCIETY OFFSHORE& POLAR ENGINEERS, 2006)
Rubble-mound breakwaters are subject not only to wave action but, also, to other types of environmental loading, such as earthquakes. The design of coastal structures should take into account the most relevant factors in each case, including seismic loading. The objective of this study is to present the dynamic response of breakwaters during earthquakes. An experimental work has been carried out for homogeneous breakwater structures for different seismic frequencies and amplitudes. However this paper has presented preliminary results of the study about seismic response of the rubble-mound breakwaters yet.
Keywords: Engineering